Chronic restraint stress increases sensitivity to punishment during cocaine self-administration via a dopamine D1-like receptor-mediated mechanism in prelimbic medial prefrontal cortex. (10th January 2023) - Ball, Kevin T.; Edson, Hunter
Highlights: Daily stress increases sensitivity to punishment during cocaine self-administration. We tested whether prelimbic dopamine D1 -like receptors mediate this effect. We combined stress with D1 -like receptor blockade in prelimbic cortex. D1 receptor blockade prevented the effects of stress on punished cocaine taking. Prelimbic D1 receptors mediate stress-induced decreases in punished cocaine taking. Abstract: We recently reported that male rats displayed less sensitivity to punishment during cocaine self-administration compared to females. Moreover, daily restraint stress increased sensitivity to punishment in males, while having no effect in females. The purpose of the present study was to extend these findings by determining whether chronic stress-induced dopamine release in prelimbic medial prefrontal cortex mediates the effect of stress on punished cocaine self-administration. Thus, male rats were trained to press a lever for i.v. cocaine infusions (0.50 mg/kg/infusion) paired with a discrete tone + light cue in daily 3-hr sessions. Subsequently, 50 % of the lever presses were punished by a mild footshock that gradually increased in intensity over 7 days. During the punishment phase, rats were exposed to a chronic restraint stress procedure (3 h/day) or control procedure (unstressed). Rats also received bilateral microinjections of the D1 -like receptor antagonist SCH-23390 (0.25 μg/0.5 μl/side) or vehicle (0.5 μl/side) delivered to prelimbic cortex prior to daily treatments. Relapse tests were conducted 1 and 8 days after the last punishment session. Chronically stressed rats displayed reduced cocaine self-administration during punishment relative to unstressed rats, an effect prevented by co-administration of SCH-23390 to prelimbic cortex with daily restraint. Neither stress nor SCH-23390 treatment had significant effects on subsequent relapse-like behavior. These results establish a specific role for prelimbic D1 -like receptors in chronic stress-induced suppression of punished cocaine self-administration in male rats. As such, these findings may inform novel methods to facilitate self-imposed abstinence in cocaine-dependent men.